Cyber Spaces/Social Spaces
XI, 172 p. 1 illus.
Keywords: What happens when a new social technology is imposed on the established social technology of the school? This book presents an unusual application of critical cultural analysis to a series of empirical case studies of educational uses of information and communication technologies (ICTs). Drawing on research conducted over a ten-year period in three different regions of the Anglo-American developed world, it examines themes arising from the struggle for the social spaces and emerging cyber spaces of schooling; the role of identity projects in educational change; and the paradoxes which arise from these processes. The resulting analysis offers a rich - and sobering - perspective on the rush to technologize classrooms.